Standardized catch rates in biomass for the stock of the North Atlantic blue shark (Prionace glauca) caught by the Spanish surface longline fleet in the period 1997-2013 - García-Cortés, Blanca; Ramos-Cartelle, Ana; Fernández-Costa, José; Mejuto-García, Jaime (2016)
Standardized catch rates per unit of effort (CPUE) were obtained for the stock of the North Atlantic blue shark (Prionace glauca) using General Lineal Models (GLM) for a total of 5639 trips of the Spanish surface longline fleet targeting swordfish, during the 1997-2013 period. The main factors considered were year, area, quarter, gear and ratio between swordfish and blue shark catches. The significant model explained the 84% of CPUE variability in blue shark. A major part of this variability was explained by the proxy of the targeting criteria, shown as the ratio between the two most prevalent species caught during the trip; swordfish and blue shark. Gear was identified as the second most important factor. Other factors were also significant, but less important. The standardized CPUE trend obtained suggests a stable trend of the North Atlantic blue shark stock and differs substantially from the nominal CPUE trends observed during the period considered. NO